A Prospective Study of the Family Quality of Life, Illness Perceptions, and Coping in Mothers of Children Newly Diagnosed with Autism Spectrum Disorder and Communication Difficulties - Angelos Papadopoulos; Angeliki Tsapara; Alexandros Gryparis; Dionysios Tafiadis; Nikolaos Trimmis; Panagiotis Plotas; Petros Skapinakis; Meropi Tzoufi; Vassiliki Siafaka (MDPI AG, 2024)
(1) Background: This study assesses the impact of mothers' illness perceptions about autism spectrum disorder and their coping strategies on the family's quality of life during the initial period following diagnosis and one year afterward. (2) Method: The sample consisted of 53 mothers of children newly diagnosed with autism spectrum disorder and having communication difficulties who completed the following: the Beach Center Family Quality of Life Scale, the Brief Illness Perception Questionnaire, and the Brief-COPE. (3) Results: The findings revealed a moderate family quality of life in the initial assessment and a lack of a statistically significant change one year later. Notably, statistically significant changes were observed in coping strategies, as in the second assessment, and the score in denial and self-blame decreased. Pearson and Eta analyses indicated several correlations between socio-demographic characteristics, illness perceptions, coping strategies, and family quality of life. Multiple regression analysis showed that positive reframing was positively associated with total family quality of life in the initial period following diagnosis and one year afterward, while self-blame was associated with poorer quality of life in the time after diagnosis. Furthermore, the belief about the controllability of the disorder was correlated with better family quality of life one year after the diagnosis. (4) Conclusions: Illness perceptions and coping can be considered as predictors of family quality of life outcomes one year after the diagnosis of autism spectrum disorder. The focus of interventions, apart from controlling the disorder's symptoms, should aim to strengthen specific strategies and weaken others.